Lung deposition and systemic bioavailability of different aerosol devices with and without humidification in mechanically ventilated patients. - Moustafa, Islam O.F.; Ali, Mohammed R. A.-A.; Al Hallag, Moataz; Rabea, Hoda; Fink, James B.; Dailey, Patricia; Abdelrahim, Mohamed E.A. (Heart & Lung, 2017)
Background During mechanical ventilation medical aerosol delivery has been reported to be upto two fold greater with dry inhaled gas than with heated humidity. Urine levels at 0.5 h post dose (URSAL0.5%) has been confirmed as an index of lung deposition and 24 h (URSAL24%) as index of systemic absorption. Our aim was to determine the effect of humidification and aerosol device type on drug delivery to ventilated patients using urine levels. Methods In a randomized crossover design, 36 (18female) mechanically ventilated patients were assigned to one of three groups. Groups 1 and 2 received 5000 μg salbutamol using vibrating mesh (VM) and jet nebulizers (JN), respectively, while group 3 received 1600 μg (16 puffs) of salbutamol via metered dose inhaler with AeroChamber Vent (MDI-AV). All devices were placed in the inspiratory limb of ventilator downstream from the humidifier. Each subject received aerosol with and without humidity at >24 h intervals with >12 h washout periods between salbutamol doses. Patients voided urine 15 min before each study dose and urine samples were collected at 0.5 h post dosing and pooled for the next 24 h. Results The MDI-AV and VM resulted in a higher percentage of urinary salbutamol levels compared to the JN (p < 0.05). Urine levels were similar between humidity and dry conditions. Conclusions Our findings suggest that in-vitro reports overestimate the impact of dry vs. heated humidified conditions on the delivery of aerosol during invasive mechanical ventilation.